BIOGENIC POTENTIAL OF STABILIZED SILVER NANOPARTICLES USING G. SYLVESTRAE AND THEIR BIOLOGICAL ASSAYS - Anburaj, Rajeswari; JOTHIPRAKASAM, VINOTH (International Journal of Applied Pharmaceutics, 2019)
Objective: The idea of green chemistry has gained immense fame due to replace chemical products and improves technologies to eradicate substances that are harmful to the environment. In this paper, a rapid cost-efficient method was employed using herbal extract Gymnema sylvestrae because of their biological constituents present in the sample. Methods: Phytosynthesis of AgNPs were optimized under different reaction conditions using pH, temperature, incubated at various concentrations. Analyses of particles were revealed using UV-Vis, FTIR spectrum, morphology was observed in scanning electron microscope, particle analysis was done using Diffraction Light Scattering and bioactive constituents present in plant sample was analysed by High-performance liquid chromatography. Bioefficacy of synthesised AgNPs was assessed by means of microbicidal assay against various bacteria and fungi. Results: UV and FTIR analysis reveals the presence of plant extract responsible for stabilization and efficient reduction. Peptides to proteins, polyphenols, and many other secondary metabolites involved in the bioreduction were identified. SEM micrograph reveals the nature, size and distribution of the sample. HPLC chromatogram indicated the presence of gymnemagenin responsible for their biological assays. Broad spectrum of microbicidal activity have been reported in 400 µl of biosynthesized AgNPs against Bacillus sp. (24.5 mm), and S. epidermis (22.3 mm). Conclusion: Therefore G. sylvestrae synthesized silver nanoparticles were stable and acts as a reducing and capping agent detecting the presence of biomolecules. Biosynthesised AgNPs showing excellent antimicrobial activity and future prospects of this study indicates that these nanoparticles can be applied in drug delivery.